KEBANGKITAN MAOIST SETELAH DELAPAN TAHUN BERDAMAI - Maria Adisti; Michael Agus Triyandi; M. Rajuali Aditya; Nurriza Noviyanti; Nico Renaldi (FISIP Universitas Tanjungpura, 2021)
This paper aims to explain the indication of the rise of the Maoists in controlling the region in Nepal. Maoists are an armed group that is carrying out movements in Nepal. The movement is considered part of the terrorism movement because it has created instability in the country of Nepal and caused a number of losses to the people of Nepal. In 2005, the Maoists turned into an opposition party through an MoU that had been ratified with the hope that the Maoists would turn into groups that did not carry out armed movements as they had before. However, the movements carried out by the Maoists did not change completely, indicating that the old Maoists had revived. In the following years, there were events that indicated that the Maoists revived with a new identity from the old Maoist fragments. In this study using the Theory of Constructivism to explain the issues raised. Constructivism Theory outlines can explain how social construction can influence the development of Maoist groups in Nepal. This research uses a descriptive method with a qualitative approach. The data collection technique used is the study of literature from books, journals, including data from websites that support the explanation of the phenomena raised.